Genetic variation in the MITF promoter affects skin colour and transcriptional activity in black-boned chickens. Issue 1 (2nd January 2018) - Wang, G.; Liao, J.; Tang, M.; Yu, S.
ABSTRACT: 1. Microphthalmia-associated transcription factor (MITF) plays a pivotal role in melanocyte development by regulating the transcription of major pigmentation enzymes (e.g. TYR, TYRP1 and DCT). A single-nucleotide polymorphism (SNP), c.-638T>C, was identified in the MITF promoter, and genotyping of a population ( n  = 426) revealed that SNP c.-638T>C was associated with skin colour in black-boned chickens. 2. Individuals with genotypes CC and TC exhibited greater MTIF expression than those with genotype TT. Luciferase assays also revealed that genotype CC and TC promoters had higher activity levels than genotype TT. Expression of melanogenesis-related gene (TYR) was higher in the skin of chickens with the CC and CT genotype compared to TT chickens ( P <  0.05). 3. Transcription factor-binding site analyses showed that the c.-638C allele contains a putative binding site for transcription factor sterol regulatory element-binding transcription factor 2, aryl hydrocarbon receptor nuclear translocator, transcription factor binding to IGHM enhancer 3 and upstream transcription factor 2. In contrast, the c.-638T allele contains binding sites for Sp3 transcription factor and Krüppel-like factor 1. 4. It was concluded that MITF promoter polymorphisms affected chicken skin colour. SNP c.-638T>C could be used for the marker-assisted selection of skin colour in black-boned chicken breeding.